The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1074/jbc.m115.701813
|View full text |Cite
|
Sign up to set email alerts
|

The F-box Protein Rcy1 Is Involved in the Degradation of Histone H3 Variant Cse4 and Genome Maintenance

Abstract: Cse4, a histone H3-like centromeric protein, plays critical functions in chromosome segregation. Cse4 level is tightly regulated, but the underlying mechanism remains poorly understood. We employed a toxicity-based screen to look for the degradation components involved in Cse4 regulation. Here, we show that the F-box containing protein Rcy1 is required for efficient Cse4 turnover as Cse4 degradation is compromised in yeast cells lacking RCY1. Excessive Cse4 accumulation in rcy1⌬ cells leads to growth retardati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…So far, four E3 ubiquitin ligases have been reported to mediate CENP-A Cse4 ubiquitylation. These include Psh1, Rcy1, Slx5 and Ubr1 [1719,20 • ,21 • ,22,23]. CENP-A Cse4 is protected from degradation at the centromere, while CENP-A Cse4 in chromosome arms is degraded.…”
Section: Intrinsic Features Of Cenp-a Modifications and Ccan Recruitmentmentioning
confidence: 99%
“…So far, four E3 ubiquitin ligases have been reported to mediate CENP-A Cse4 ubiquitylation. These include Psh1, Rcy1, Slx5 and Ubr1 [1719,20 • ,21 • ,22,23]. CENP-A Cse4 is protected from degradation at the centromere, while CENP-A Cse4 in chromosome arms is degraded.…”
Section: Intrinsic Features Of Cenp-a Modifications and Ccan Recruitmentmentioning
confidence: 99%
“…Ubiquitination of substrates for proteasomemediated degradation is catalyzed by three classes of enzymes, namely the E1 ubiquitin-activating enzyme, E2 ubiquitin-conjugating enzyme and E3 ubiquitin ligase [20][21][22]. Studies with budding yeast have identified the non-essential E3 ubiquitin ligase Psh1, Sumo-targeted ubiquitin ligases (STUbLs) Slx5, Slx8 and the Skp-Cullin-F-box (SCF)-Rcy1 in ubiquitin-mediated proteolysis of overexpressed Cse4 [23][24][25][26][27][28]. Both the N-terminus and the CENP-A targeting domain (CATD) in the C-terminus of Cse4 are required for Psh1-mediated proteolysis of overexpressed Cse4 [19,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Ubiquitylation has been reported to prevent the ectopic localization of Cse4 by triggering its degradation, and the E3 ubiquitin ligases Psh1, Rcy1, Slx5, and Ubr1 have been shown to ubiquitylate Cse4 (Fig. 5) (Au et al 2013; Cheng et al 2017; Cheng et al 2016; Collins et al 2004; Hewawasam et al 2010; Ohkuni et al 2016; Ranjitkar et al 2010). While Psh1 ubiquitylates Lys-4, Lys-131, Lys-155, Lys-163 and Lys-172 (Hewawasam et al 2010), Slx5-mediated proteolysis of Cse4 is directed by sumoylation at Lys-65 (Ohkuni et al 2018) (Fig.…”
Section: Diversity Of Cenp-a Modifications Across Speciesmentioning
confidence: 99%